WhatsApp, comunicación móvil y participación política: un estudio cuantitativo en Ecuador - Zumárraga-Espinosa, Marcos (2021)
This work explores the relationship between the different political uses of WhatsApp and the political participation behaviors in the Ecuadorian context. With the purpose of achieving a more detailed understanding, political participation was classified into three specific modes of action: offline conventional, offline protest and online. On the other hand, the political use of WhatsApp was classified into three types:a) consumption of political information, b) political expression and discussion, and c) contact with online political groups. Using survey data collected in the Metropolitan District of Quito (Ecuador) in 2018, multiple regression analyses indicate that the consumption of political information via WhatsApp only significantly influences political protest actions. On the contrary, the political expression and discussion through thismobile application produce mobilizing effects on all the analyzed participation forms: a consistent effect also observed when WhatsApp is used for interaction with online political groups. The final section discusses the findings of the study taking into account the previous research on the democratic effects of WhatsApp.